Understanding Dermatologic Concerns Among Persons Experiencing Homelessness: A Scoping Review and Discussion for Improved Delivery of Care. Issue 6 (November 2021) - Adly, Merna; Woo, Taylor Evart; Traboulsi, Danya; Klassen, David; Hardin, Jori
There is a paucity of information surrounding dermatologic care for persons experiencing homelessness (PEH). This scoping review aims to map existing literature and provide a summary of the most common cutaneous manifestations among PEH, risk factors for dermatologic disease, describe any reported interventions, as well as identify research gaps for future studies. Search strategies developed for MEDLINE and hand searching yielded 486 articles. Out of the 486 articles screened, 93 articles met the inclusion criteria. The majority were cohort studies, cross-sectional studies, and case-control studies concentrated in North America and Europe. Excluding the pediatric population, the prevalence of dermatologic conditions ranged from 16.6% to 53.5%. Common skin conditions described in PEH were: acne, psoriasis, seborrheic dermatitis, atopic dermatitis, and lichen simplex chronicus. There were no studies comparing the extent or severity of these cutaneous diseases in PEH and the general population. PEH have a higher prevalence of skin infections and non-melanoma skin cancers. This scoping review has direct implications on public health interventions for PEH and highlights the need for evidence-based interventions to provide optimum and safe dermatologic healthcare for PEH. We propose several recommendations for improved care delivery, including addressing upstream factors and comorbidities impacting skin health, providing trauma informed care, reducing barriers to care, preventing and managing skin conditions, as well as including PEH in the planning and implementation of any proposed intervention.